The Influence of Islamic Investment Literacy and Investment Motivation on Islamic Investment Decisions Among Generation Z University Students in Surakarta - Annisa Rahmadiani; Muhammad Sholahuddin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
With investment risk perception acting as a mediator, the study examines how Islamic investment literacy and investment desire affect factors influencing Islamic investment decision-making among Generation Z university students in Surakarta. 150 enrolled students aged 18 to 27 were administered questionnaires as part of this study's quantitative research design and survey methodology. Using SmartPLS software, the data were next examined using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings show that students' decisions about Islamic investments are positively and statistically significantly impacted by Islamic investment knowledge. Likewise, investment motivation was found to influence Islamic investment decision-making positively. Moreover, risk perception functions as a significant mediating mechanism through which Islamic investment literacy and investment motivation influence Islamic investment decision-making. The originality of this research lies in integrating Islamic investment literacy and investment motivation within a unified structural framework that explicitly positions risk perception as a mediating factor among Generation Z students, a group that has received limited attention in previous Islamic investment research. While earlier studies mainly focused on direct relationships, this research provides empirical evidence of the indirect pathways through which literacy and motivation shape investment decisions via perceived risk. From a theoretical perspective, this study contributes by proposing an extended behavioral model of Islamic investment decision-making that incorporates cognitive, motivational, and risk perception dimensions. In practice, the results have important implications for educational institutions and financial regulators in formulating targeted literacy initiatives and policy strategies to increase Islamic investment participation among younger generations in alignment with Islamic values.